Finding Someone to Blame: The Link Between COVID-19 Conspiracy Beliefs, Prejudice, Support for Violence, and Other Negative Social Outcomes - Šrol, Jakub; Čavojová, Vladimíra; Ballová Mikušková, Eva (Frontiers in Psychology, 2022)
One of the appeals of conspiracy theories in times of crises is that they provide someone to blame for what has happened. Thereby, they increase distrust, negative feelings, and hostility toward implicated actors, whether those are powerful social outgroups or one’s own government representatives. Two studies reported here examine associations of COVID-19 conspiracy theories with prejudice, support for violence, and other and negative social outcomes. In Study 1 (N = 501), the endorsement of the more specific conspiracy theories about the alleged role of China was associated with more prejudiced views of Chinese and Italian people. In Study 2 (N = 1024), lowered trust in government regulations and increased hostility associated with the COVID-19 and generic conspiracy beliefs were correlated with justification of and willingness to engage in non-compliance with regulations, violent attacks on 5G masts, and anti-government protests. Across both of the studies, higher exposure to news about COVID-19 was associated with lower endorsement of conspiracy theories, but also with increased feelings of anxiety and lack of control, which in turn were correlated with higher COVID-19 conspiracy beliefs endorsement. We highlight the potential social problems which are associated with the widespread endorsement of COVID-19 conspiracy theories.